Pengaruh Tingkat Absensi Dan Insentif Terhadap Kinerja Karyawan Pada PT. Multi Teknik Telaga Indonesia Jakarta Barat - Sheavy Diani; Irwin Ananta Vidada; Seno Sudarnomo Hadi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
PT Multi Teknik Telaga Indonesia is a distributor for European gearbox and electric motor manufacturers. PT Multi Teknik Telaga Indonesia is one of the sole agents of electric motor/gear motor products and one of the largest gear companies. Based on the objectives and form of the research conceptual framework, the approach used in this research is quantitative. In this study, simultaneously the level of attendance and incentives has a significant effect on employee performance with the F test value obtained of 28,286 with a sig value. 0.000 because the probability is below 0.05 or 0.000 0.05, the multiple linear regression model can be used to predict employee performance or it can be said that the Attendance Rate (X1) and Incentives (X2) simultaneously affect Employee Performance (Y).PT. Multi Teknik Telaga Indonesia to implement an effective and efficient employee attendance attendance system, so as to facilitate the human resource management process, save costs and time and increase employee productivity and assess employee performance by considering factors such as attendance and incentive levels, so as to provide a more complete picture of employee performance.